Possibilities of osmotic adaptation of the shrimp Palaemon adspersus to low salinity media - Crăciun, Margareta; Crăciun, V.; Neacșu, I.; Dimoftache, Gabriela (Cercetări Marine - Recherches Marines, 2026)
The effects of low salinities (8 and 5‰) on hydric and mineral balance of males and females of Palaemon adspersus were studied. In hypo-saline media, both sexes showed noticeable possibilities of osmoregulation due to modifications of passive permeability of the cell membranes and by stimulation of the active ionic transport mechanisms.